2018
DOI: 10.1163/1568539x-00003508
|View full text |Cite
|
Sign up to set email alerts
|

Network size, structure, and pathogen transmission: a simulation study comparing different community detection algorithms

Abstract: Social substructure can influence pathogen transmission. Modularity measures the degree of social contact within versus between “communities” in a network, with increasing modularity expected to reduce transmission opportunities. We investigated how social substructure scales with network size and disease transmission. Using small-scale primate social networks, we applied seven community detection algorithms to calculate modularity and subgroup cohesion, defined as individuals’ interactions within subgroups pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In addition to the properties of individuals, variation in pairwise interactions can produce structure in the overall network. In primate social groups, for example, subgroups often emerge, within which interactions are more frequent relative to interactions between subgroups [59,60]. In social network theory, subgrouping is measured using metrics such as community modularity [61].…”
Section: (B) Social Network and Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the properties of individuals, variation in pairwise interactions can produce structure in the overall network. In primate social groups, for example, subgroups often emerge, within which interactions are more frequent relative to interactions between subgroups [59,60]. In social network theory, subgrouping is measured using metrics such as community modularity [61].…”
Section: (B) Social Network and Transmissionmentioning
confidence: 99%
“…In social network theory, subgrouping is measured using metrics such as community modularity [61]. High modularity can decrease transmission because fragmentation of the network and cohesion within subgroups tend to 'trap' parasites within a subgroup, leading to lower outbreak size and delayed transmission dynamics [53,57,58,60,62]. These features of network structure and individual centrality can, therefore, have important applications to conservation management strategies.…”
Section: (B) Social Network and Transmissionmentioning
confidence: 99%
“…For an overview, see Yang, Algesheimer, and Tessone (2016). Until recently, no research had investigated what would be the impact of choosing different community detection algorithms in the results (Aldecoa & Marín, 2013; Sumner, McCabe, & Nunn, 2018). Sumner et al (2018) showed possible variations between those different algorithms; therefore, we recommend to choose carefully an appropriate community detection algorithm for the question of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, no research had investigated what would be the impact of choosing different community detection algorithms in the results (Aldecoa & Marín, 2013; Sumner, McCabe, & Nunn, 2018). Sumner et al (2018) showed possible variations between those different algorithms; therefore, we recommend to choose carefully an appropriate community detection algorithm for the question of interest. Unfortunately, it is only recently that these questions have been addressed and a general guideline cannot be provided except that multiple algorithms may be used and the results may be compared.…”
Section: Introductionmentioning
confidence: 99%
“…We focus on modularity over other indices, such as nestedness or centralization, because the epidemiological consequences of modularity are better studied and intuitive: modularity reflects subdivision of a network into more distinct units, which are expected to slow disease transmission in the same way that quarantines reduce spread in human populations. To ensure that changes in modularity reflect changes in transmission [ 61 , 62 ], we also simulate disease spread on the networks, focusing on speed of transmission.…”
Section: Introductionmentioning
confidence: 99%